Dynamic of bio-geometric profile indicators of children's with functionally one ventricle posture at stage of physical rehabilitation - V.V. Vitomskiy; O.B. Lazarіeva; E.V. Imas; V.A. Zhovnir; I.N. Emets (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Purpose: to assess dynamic of bio-geometric profile quantitative indicators in children with functionally one ventricular at stages of physical rehabilitation. Material: 35 patients were examined during hospital stay and when leaving hospital. Indicators were registered with the help of photo metering and program Ergotherapy. Results: in children we registered great number of posture disorders in frontal (94.3%) and sagittal planes (97.1%). In frontal plane the angles, pointing at significant asymmetry of upper limbs in respect to horizontal plane, were increased. In sagittal plane we received angles, which pointed at presence of thoracic kyphosis and lumbar lordosis. After surgery and stationary stage of rehabilitation static changes were registered in insignificant quantity of the studied angles. After post-clinical physical rehabilitation stage we registered reduction of angles' values and their approaching to norm. Conclusions: physical rehabilitation at stationary and port clinical stages with the help of correcting exercises positively influence on restoration of posture after surgery and its improvement in the future.